Abrogation “Privity of Contract” Due To One Sided Withdrawal of A Third Party As An Emergency Contact From Borgtocht Perspective - Panjaitan, Wijaya Natalia (Batulis Civil Law Review, 2024)
Introduction: The inclusion of a third party's personal data as an emergency contact in an agreement is often done one-sidedly by the debtor, to the detriment of the third party who is often disturbed to find the debtor's whereabouts, even though the third party does’nt know and never agreed to have his personal data included as an emergency contact.Purposes of the Research: This research aims to find out the abrogation of the principle of privity of contract in the context of one-sided withdrawal of a third party as an emergency contact in the perspective of personal guarantee law (borgtocht).Methods of the Research: This research is using the normative juridical method. The approach is through legislation, which is the Civil Code and conceptual approaches.Results of the Research: The principle of privity of contract in the perspective of personal guarantee law (borgtocht) will be invalid and cannot be applied to emergency contact if the third party whose name is included is not asked for prior approval by the parties in the agreement.